INVESTIGATING YOUNG LEARNERS PERCEPTION AND MORAL VALUES ON LISTENING SKILL THROUGH WATCHING MOVIE “DORA: THE LOST CITY OF GOLD” - Ina Rohiyatussakinah; Sri Ardiani; Ida Nuraida; Nur Hidayanti (FKIP, Universitas Banten Jaya, 2022)
The aim of the research was to investigate young learners perceptions and moral values on listening while English language teaching for young learner by having